Orally administered extracellular vesicles from Salmonella-infected macrophages confer protective immunity in vivo - Bhimani, Saloni; Canas, Jorge J.; Enslow, Samantha M.; Mulcare, Ryan; Ferraro, Mariola J. (Frontiers in Immunology, 2025)
Salmonella is a leading cause of foodborne illness in the United States and worldwide. This enteric pathogen deploys various mechanisms to evade the intestinal mucosal barrier to enhance its survival and further infect systemic tissues. Commercially available vaccines against Salmonella are currently restricted to the serovar Typhi, while none are currently approved for non-typhoidal Salmonella (NTS) serovars, which are becoming increasingly resistant to antibiotics. Due to the lack of effective vaccines against NTS infections, novel oral vaccination strategies have garnered significant interest, owing to their protective abilities at the susceptible sites of infection. We previously reported that mice immunized intranasally with small extracellular vesicles (sEVs) derived from Salmonella-infected macrophages protect mice against lethal Salmonella challenge. In the present study, we used an oral route of administration of sEVs to determine their protective abilities in vivo. Remarkably, orally administered sEVs from Salmonella-infected macrophages conferred significant host protection, marked by improved survival post-challenge and reduction in tissue bacterial burdens. Additionally, immunized mice exhibited robust serological responses, including elevated levels of both whole-Salmonella and OmpA-specific IgG antibodies. Collectively, these findings show the potential of orally delivered sEVs as a promising, cell-free vaccine platform for protection against salmonellosis.